Implementasi Kebijakan E-Procurement di Kabupaten Buton Selatan - Zainul Abidin; La Didi; Yuharsi (Sawala : Jurnal Administrasi Negara, 2021)
E-procurement is the government's effort to improve public services and develop good governance. This study aims to explain the implementation as well as the e-procurement model in South Buton Regency. Data collection techniques using interviews, observation, and document studies. The results show that the implementation of e-procurement in the South Buton Regency has been carried out even though there are several problems. The e-procurement implementation model in South Buton Regency shows that the variables that affect performance are the disposition of the implementor and the characteristics of the implementing agent. The main variable is the disposition of the implementor because the implementors in South Buton Regency know, understand, accept and implement the e-procurement policy as stipulated in Presidential Regulation 16 of 2018 concerning the procurement of government goods/services. Implementors have a strategy, namely by holding concurrent positions as happened in the election working group, working more outside working hours, also trying to maximize funding sources and limited facilities and infrastructure. On the other hand, resources affect the characteristics of implementing agents where regional apparatus organizations need resources, both human resources, financial resources, and the availability of facilities and infrastructure in implementing programs and activities.